2008
DOI: 10.1111/j.1540-6237.2008.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Hurricane Katrina Employment Recovery: The Interaction of Race and Place*

Abstract: The mass migrations, infrastructure decimation, and widespread impact zone make Hurricane Katrina an especially difficult disaster from which to recover. Employment is an important aspect of effective disaster recovery. The purpose of this article is to examine determinants of employment recovery approximately one month and one year after Hurricane Katrina. Copyright (c) 2008 by the Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 24 publications
(26 reference statements)
2
36
0
Order By: Relevance
“…Zottarelli (2008) used two waves of survey to examine the determinants of employment recovery status in New Orleans after Hurricane Katrina from the point of view of the interaction between location and race. Although displacement, income, and home ownership were significant determinants of job recovery, women were almost twice as likely to fail to recover employment conditions than men because, as Zottarelli concluded, they were expected to take care of their family members and generally had to remain away from their jobs for longer than men.…”
Section: Climate Change Adaptation and Its Effects On Gender Issuesmentioning
confidence: 99%
“…Zottarelli (2008) used two waves of survey to examine the determinants of employment recovery status in New Orleans after Hurricane Katrina from the point of view of the interaction between location and race. Although displacement, income, and home ownership were significant determinants of job recovery, women were almost twice as likely to fail to recover employment conditions than men because, as Zottarelli concluded, they were expected to take care of their family members and generally had to remain away from their jobs for longer than men.…”
Section: Climate Change Adaptation and Its Effects On Gender Issuesmentioning
confidence: 99%
“…The study suggested that relief for any one point within the supply chain did not necessarily guarantee relief for any other components [16]. Regardless of improvement, impeded environments existed after calamity affecting normalcy [14,15,16].…”
mentioning
confidence: 99%
“…Zottarelli [14] investigated recovery associated with Hurricane Katrina from an employment perspective. Individuals who moved exhibited less chance of experiencing recovered employment [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these bleak labor market prospects, scholars find no association between these objective measures and individuals' return migration (Fussell et al, 2010, Zottarelli, 2008.…”
mentioning
confidence: 99%